The Effect Of Continuity Of Care Against Weight and Length Of Newborn Body In Rejoyoso Village - Nurya Viandika; Alifia Candra Puriastuti (Universitas STRADA Indonesia, 2020)
Stunting is still a nutritional problem for the community both at national and international levels. long and low birth weight history in is one of the risk factors of stunting. This research identifies whether there is an effect of continuity of care on length and birth weight. So that you can get a way to prevent stunting as early as possible. This research was conducted in Rejoyoso Village with a population of mothers who have babies aged 0-6 months, with a retrospective approach and the source of research data is the maternat book record. The research data were analyzed by chi square, and the result of birth length x2 count 5,605> x2 table 3,841 and the result of birth weight x2 count 5,029> x2 table 3,841. So the interpretation obtained from each variable is rejecting H0 or there is a continuity of care effect on length and birth weight